2001
DOI: 10.1177/001440290106700202
|View full text |Cite
|
Sign up to set email alerts
|

Caseload in Special Education: An Integration of Research Findings

Abstract: Despite escalating special education costs and increasing student needs, policies governing special education caseload remain inconsistent, and implementation is even more variable. This article considers links between (a) instructional group size and student engagement, (b) caseload and academic achievement, and (c) caseload and special education teacher attrition. Findings suggest that (a) larger caseloads and instructional group sizes negatively impact student math and reading achievement; (b) severity of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 15 publications
3
52
0
Order By: Relevance
“…More than half of the states currently have initiatives to reduce class size (Russ, Chiang, Rylance, & Bongers, 2001;Wexler et al, 2001). Yet, research on caseload, class size, and achievement in special education is relatively rare.…”
Section: Caseloadsmentioning
confidence: 99%
See 1 more Smart Citation
“…More than half of the states currently have initiatives to reduce class size (Russ, Chiang, Rylance, & Bongers, 2001;Wexler et al, 2001). Yet, research on caseload, class size, and achievement in special education is relatively rare.…”
Section: Caseloadsmentioning
confidence: 99%
“…Yet, research on caseload, class size, and achievement in special education is relatively rare. In a review of the research, Russ et al (2001) found that larger caseloads negatively impact students' math and reading achievement, individualization is more likely to occur in smaller groups, student engagement and achievement increase with smaller group sizes, and high teacher attrition and large caseloads seem to be related.…”
Section: Caseloadsmentioning
confidence: 99%
“…Researchers have linked job satisfaction to teacher attrition (Bobbitt, Leich, Whitner, & Slynch, 1994;Russ, Chiang, Rylance, & Bongers, 2001) practice related variables such as salaries, credentialing, opportunities for promotion, supervision, recognition, student behavior, working conditions, and sense of autonomy (Evans, 1986). According to Shan (1998), teacher job satisfaction is a predictor of teacher retention, a determinant of teacher commitment, and in turn a contributor to school effectiveness.…”
Section: Teachers' Job Satisfactionmentioning
confidence: 99%
“…This demand could also be influenced by teacher case loads, which have been the focus of concern for many professionals in recent years (Russ et al, 2001). …”
Section: Student Enrollmentmentioning
confidence: 99%